Bridging the Gap: Aligning an English for Business Communication Syllabus with Workplace Demands through Professional Insights - Quyen Anh, Tran Nguyen (VNU Journal of Science: Education Research, 2026)
This study seeks to address discrepancies between English for business communication curricula and industry requirements by soliciting recommendations from industry professionals to: i) Identify the communication skills that should be emphasized in an English for business communication syllabus tailored to teach business English at a university in Vietnam; and ii) Determine how the syllabus content should be revised to meet the actual workplace communication needs. The findings indicate that industry professionals emphasize the importance of communicative competence, which involves not only the mastery of specific communication skills but also the demonstration of appropriateness and effectiveness. Although the selected syllabus topics were deemed relevant to workplace needs, the specific functions outlined under each chapter were identified as problematic. They tended to prioritize safer, less challenging forms of communication and lacked a logical progression. The findings provide valuable insights aimed at enhancing the relevance and effectiveness of English for business communication curricula.